MicroRNAs and Natural Compounds Mediated Regulation of TGF Signaling in Prostate Cancer - Javed, Zeeshan; Khan, Khushbukhat; Rasheed, Amna; Sadia, Haleema; Raza, Shahid; Salehi, Bahare; Cho, William C.; Sharifi-Rad, Javad; Koch, Wojciech; Kukula-Koch, Wirginia; Głowniak-Lipa, Anna; Helon, Paweł (Frontiers in Pharmacology, 2021)
Prostate cancer (PCa) is with rising incidence in male population globally. It is a complex anomaly orchestrated by a plethora of cellular processes. Transforming growth factor-beta (TGF-β) signaling is one of the key signaling pathways involved in the progression and invasiveness of PCa. TGF-β signaling has a dual role in the prostate cancer making it difficult to find a suitable therapeutic option. MicroRNAs (miRNAs) mediated regulation of TGF-β signaling is responsible for the TGF- β paradox in PCa. These are small molecules that modulate the expression of target genes by binding to them and regulate cancer progression. Owing to these characteristics miRNAs interaction with different signaling cascades (TGF-β signaling) is of great value for devising new diagnostic and therapeutic options for PCa. Natural compounds have been extensively studied over the years due to their low cytotoxicity and high efficacy. Here we discuss the involvement of TGF- β signaling in PCa with the interplay between miRNAs and TGF- β signaling for devising new diagnostic/prognostic options and also review the role of natural compounds for the development of new therapeutics for PCa.